Air Pollution Mediates the Association between Human Mobility and COVID-19 Infection - Kang Lo; Nguyen Thanh Tung; Chih-Da Wu; Huynh Nguyen Xuan Thao; Hoang Ba Dung; Tran Phan Chung Thuy; Hsiao-Chi Chuang (Aerosol and Air Quality Research)
Abstract The effects of the restriction policies on human mobility and on the prevention of SARS-CoV-2 (coronavirus disease 2019 (COVID-19) transmission were reported. The efficiency of human mobility restriction due to the social distancing measures of cities on preventing SARS-CoV-2 spread remains unclear. The objective of this study was to investigate the mediating effects of air pollution on the association between human mobility and daily confirmed COVID-19 cases. Daily mobility data (i.e., walking, driving, and using public transport), air pollutants, and confirmed COVID-19 cases were collected in Taiwan during 1 to 30 May 2021. Associations of air pollution with 7-day-lag confirmed COVID-19 cases and with mobility were examined by linear regression models, while the mediating effects were assessed using a PROCESS analysis. We observed that an increase in air pollution was associated with an increase in confirmed COVID-19 cases (p < 0.05). We found that 1 min spent on mobility was associated with changes in air pollution levels (p < 0.05). We observed that levels of particulate matter with an aerodynamic diameter of < 10 µm (PM10), PM2.5, NO2, and CO mediated associations of walking, driving, and using public transport with confirmed COVID-19 cases (p < 0.05). Our findings suggest that the nationwide restrictions (social distancing measures) may reduce human mobility and activities, which was associated with a decrease in confirmed COVID-19 cases due to the mediating effects of air pollution. Reductions in human mobility and air pollution could be effective measures for controlling COVID-19 transmission.